Kagami-Ogata Syndrome: Case Series and Review of Literature - Rishika P. Sakaria; Roya Mostafavi; Stephen Miller; Jewell C. Ward; Eniko K. Pivnick; Ajay J. Talati (Thieme Medical Publishers, Inc., 2021)
Kagami-Ogata syndrome (KOS) (OMIM #608149) is a genetic imprinting disorder affecting chromosome 14 that results in a characteristic phenotype consisting of typical facial features, skeletal abnormalities including rib abnormalities described as "coat hanger ribs," respiratory distress, abdominal wall defects, polyhydramnios, and developmental delay. First identified by Wang et al in 1991, over 80 cases of KOS have been reported in the literature. KOS, however, continues to remain a rare and potentially underdiagnosed disorder. In this report, we describe two unrelated male infants with differing initial presentations who were both found to have the characteristic "coat hanger" rib appearance on chest X-ray, raising suspicion for KOS. Molecular testing confirmed KOS in each case. In addition to these new cases, we reviewed the existing cases reported in literature. Presence of polyhydramnios, small thorax, curved ribs, and abdominal wall defects must alert the perinatologist toward the possibility of KOS to facilitate appropriate molecular testing. The overall prognosis of KOS remains poor. Early diagnosis allows for counseling by a multidisciplinary team and enables parents to make informed decisions regarding both pregnancy management and postnatal care.